Nanoparticles containing constrained phospholipids deliver mRNA to liver immune cells in vivo without targeting ligands. Issue 3 (27th May 2020) - Gan, Zubao; Lokugamage, Melissa P.; Hatit, Marine Z. C.; Loughrey, David; Paunovska, Kalina; Sato, Manaka; Cristian, Ana; Dahlman, James E.
Abstract: Once inside the cytoplasm of a cell, mRNA can be used to treat disease by upregulating the expression of any gene. Lipid nanoparticles (LNPs) can deliver mRNA to hepatocytes in humans, yet systemic non‐hepatocyte delivery at clinical doses remains difficult. We noted that LNPs have historically been formulated with phospholipids containing unconstrained alkyl tails. Based on evidence that constrained adamantyl groups have unique properties that can improve small molecule drug delivery, we hypothesized that a phospholipid containing an adamantyl group would facilitate mRNA delivery in vivo. We quantified how 109 LNPs containing "constrained phospholipids" delivered mRNA to 16 cell types in mice, then using a DNA barcoding‐based analytical pipeline, related phospholipid structure to in vivo delivery. By analyzing delivery mediated by constrained phospholipids, we identified a novel LNP that delivers mRNA to immune cells at 0.5 mg/kg. Unlike many previous LNPs, these (a) did not preferentially target hepatocytes and (b) delivered mRNA to immune cells without targeting ligands. These data suggest constrained phospholipids may be useful LNP components.